Morphology and Halochamigrene Metabolite Content of Laurencia majuscula (Rhodomelaceae, Ceramiales) from the Spratly Islands - Santhanaraju Vairappan, Charles; Siew-Moi, Phang (Malaysian Journal of Science, 2005)
The population of the red alga Laurencia majuscula (Harvey) Lucas (Rhodomelaceae, Ceramiales) from Spratly Islands was characterized on the basis of both morphology and its inherently available halogenated metabolite content. Specimens of Laurencia population were larger in size and had more slender thalli than those collected from other regions of Malaysian waters. Furthermore, the population had three halochamigrene metabolites, elatol (1) (5.5%), iso-obtusol (2) (4.2%) and rogiolol (3) (2.8%), as its secondary metabolites. Presence of elatol (1) and iso-obtusol (2) in L. majuscula from this location confirms their importance as chemotaxonomical marker for this particular species in the Malaysian waters. Hence, suggesting absence of "chemical races" within this species. These compounds also showed biological activity against marine bacteria, human pathogenic bacteria and yeast.